Highly Integrated, Wearable Carbon‐Nanotube‐Yarn‐Based Thermoelectric Generators Achieved by Selective Inkjet‐Printed Chemical Doping (Adv. Energy Mater. 25/2022). Issue 25 (7th July 2022) - Park, Kyung Tae; Cho, Young Shik; Jeong, Inho; Jang, Doojoon; Cho, Hyeon; Choi, Yoohyeon; Lee, Taemin; Ko, Youngpyo; Choi, Jaeyoo; Hong, Soo Young; Oh, Min‐Wook; Chung, Seungjun; et al.
Abstract : Wearable Electronics In article number 2200256, Seungjun Chung, Chong Rae Park, Heesuk Kim and co‐workers fabricate a highly integrated, wearable carbon‐nanotube‐yarn (CNTY)‐based thermoelectric generator (TEG) by precisely doping CNTY into p ‐ and n ‐type segments via picoliter scale inkjet printing (depicted as splash of solution). The TEG can conformably wrap around bodies and harvest electric energy directly from body heat.